1981
DOI: 10.1063/1.92741
|View full text |Cite
|
Sign up to set email alerts
|

ZnI (BX) laser: 600–604 nm

Abstract: Erratum: "Epitaxial growth of ZnY ferrite films by pulsed laser deposition" [J. Discharge pumped ZnI (599-606 nm) and CdI (653-662 nm) amplifiers Appl. Phys. Lett. 42, 20 (1983); 10.1063/1.93750 Fluorescence lifetime studies of NO2. I. Excitation of the perturbed 2 B 2 state near 600 nm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Such transition has received significant attention among the other zinc monohalides ever since the demonstration of the ZnI lasing. 17 Our spectroscopic constants of the excited 2 Σ + states are compared to those computed theoretically. 10,11 Although diabatic approximation has yielded better vibrational frequency of the (2) 2 Π state, reasonable agreements are shown for the other constants.…”
Section: R a F Tmentioning
confidence: 99%
“…Such transition has received significant attention among the other zinc monohalides ever since the demonstration of the ZnI lasing. 17 Our spectroscopic constants of the excited 2 Σ + states are compared to those computed theoretically. 10,11 Although diabatic approximation has yielded better vibrational frequency of the (2) 2 Π state, reasonable agreements are shown for the other constants.…”
Section: R a F Tmentioning
confidence: 99%
“…The potentials energy curves of the low lying states of CdBr and CdI are presented in figures (5)(6)(7)(8). It is found that the electronic ground states of CdBr and CdI is the X 2 Σ + state with R e = 2.564 Å and R e = 2.749 Å respectively.…”
Section: Cdbr and CDI Moleculesmentioning
confidence: 99%
“…The analogy between the transitions of ZnI and CdI [8][9][10][11] and those that are demonstrated on the bluegreen lasing on the transition between B 2 Σ + -X 2 Σ + of mercury mono-halides [12][13][14][15][16] inspired studies on the composing molecules of such laser systems. Inspired by the similarity between the valence electronic structure of cadmium monohalides and the first exploratory laser-cooled SrF diatomic 17,18 with the 3d orbitals fully occupied, we are encouraged to investigate the low-lying electronic states of cadmium monohalides.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of the blue-green lasing on the B 2 Σ þ -X 2 Σ þ transition of mercury mono-halides [1][2][3][4][5] and the analogous transitions of ZnI and CdI [6][7][8] have motivated subsequent studies to be carried out on such laser systems and their composing molecules. Lipson and his coworker [9] presented the fluorescence excitation spectra of ZnI from which the potential energy curves of the three lowlying spin-orbit states and the equilibrium bond length of the B 2 Σ þ state were reported.…”
Section: Introductionmentioning
confidence: 99%